KEEFEKTIFAN MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISIONS DENGAN PENDEKATAN KONTEKSTUAL TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS IV SD N LOANO - Devi Damayanti; Lisa Virdinarti Putra (Jurnal Dedikasi Pendidikan, 2024)
: This study aims to determine the effect of using the Student Teams Achievement Divisions model with a contextual approach. This study uses a quantitative approach using quasi-experimental methods. Determination of the sample in this study is purposive sampling. The sample taken in this study was class IV SD N Loano. Where class IV A is the control class and class IV B is the experimental class. The results showed that there was an influence of the Student Teams Achievement Divisions (STAD) learning model with a contextual approach to increasing conceptual understanding. This is evidenced by a significant value of 0.042 <0.005. The conclusion from this study is that the Student Teams Achievement Divisions (STAD) learning model with a contextual approach has an influence in increasing students' understanding of mathematical concepts.